Does privatization hurt workers? Lessons from comprehensive manufacturing firm panel data in Hungary, Romania, Russia, and Ukraine - J. David Brown; John S. Earle; Almos Telegdy (W.E. Upjohn Institute for Employment Research, 2006)
We estimate the effects of privatization on firm-level wages and employment in four transition economies. Applied to longitudinal data on manufacturing firms, our fixed effect and random trend models consistently fail to support workers' fears of job losses from privatization, and they never imply large negative effects on wages; only for domestic privatization in Hungary and Russia are small (3-5%) negative wage effects found. Privatization to foreign investors has positive estimated impacts on both employment and wages in all four countries. The negligible consequences of domestic privatization for workers result from effects on scale, productivity, and costs that are large but offsetting in Hungary and Romania, and from small effects of all types in Russia and Ukraine. The positive employment outcome under foreign ownership results from a substantial scale-expansion effect that dominates the productivity-improvement effect, and the positive wage outcome from a productivity effect that dominates the effect on costreduction.
Keywords: D21; G34; J23; J31; L33; P31; 330; privatization; employment; wages; foreign ownership; Hungary; Romania; Russia; Ukraine; Privatisierung; Eigentümer; Lohn; Beschäftigung; Verarbeitendes Gewerbe; Transformationsstaaten; Ungarn; Rumänien; Russland; Ukraine; Ausländisch